Efektifitas pendidikan kesehatan tentang imunisasi Tetanus toksoid (tt) terhadap pengetahuan ibu hamiltentang imunisasi tt - Aprida, Sriwahyu -; Utami, Sri -; Hasneli, Yesi - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determined the effectiveness of health education about tetanus toxoid immunization for increasing knowledge pregnant women about tetanus toxoid immunization. The design of this research was Quasy experiment designed by Pre-posttest with control group were divided into experiment group and control group. The research was conducted on pregnant women in the â€œPuskesmas Harapan Raya Pekanbaruâ€. The total sample were 30 people who were taken by using purposive sampling techniques by noticing to the inclusion criteria. Measuring instruments that used in both groups were questionnaires that have been tested for validity and reliability. Analysis was used univariate and bivariate analyzes using dependent test and independent test. The results showed that health education about tetanus toxoid immunization was effective for improving knowledge pregnant women about tetanus toxoid immunization with p value (0.000) < Î± (0,05). The results of this research was recommend to every health care have to giving health education about tetanus toxoid immunization by using power point and leaflet media to increasing knowledge of pregnant women about tetanus toxoid immunization. Â  Key words : Health education, knowledge, tetanus toxoid immunization